2000
DOI: 10.1116/1.1288945
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and characterization of a micromachined 5 mm inductively coupled plasma generator

Abstract: Experimental and theoretical characterization of an inductively coupled plasma source J. Appl. Phys. 90, 587 (2001); 10.1063/1.1375009Stabilizing inductively coupled plasma source impedance and plasma uniformity using a Faraday shieldThe electron temperature and ion density produced by a microfabricated plasma generator are characterized in both argon gas and air. The plasma generator sustains a discharge by inductively coupling 450 MHz rf power into a small ͑10 mm diameter͒ vacuum chamber. The inductively cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 11 publications
1
30
0
Order By: Relevance
“…Small microfabricated ICPs (mICP) have also been developed in recent years. [16][17][18][19][20][21][22][23][24][25][26] Whereas large ICPs are typically operated at a frequency of 13.56 MHz, it has been shown that the optimum frequency for plasma generation increases to 460 MHz when the coil diameter is reduced to 5 mm. 17 It was found that the electron density increases with the frequency and is about an order of magnitude higher than in a large scale ICP as a result of the large surface-to-volume ratio of small discharges.…”
Section: High-frquency Plasmasmentioning
confidence: 99%
See 1 more Smart Citation
“…Small microfabricated ICPs (mICP) have also been developed in recent years. [16][17][18][19][20][21][22][23][24][25][26] Whereas large ICPs are typically operated at a frequency of 13.56 MHz, it has been shown that the optimum frequency for plasma generation increases to 460 MHz when the coil diameter is reduced to 5 mm. 17 It was found that the electron density increases with the frequency and is about an order of magnitude higher than in a large scale ICP as a result of the large surface-to-volume ratio of small discharges.…”
Section: High-frquency Plasmasmentioning
confidence: 99%
“…A one-mask fabrication process was used for the matching network and the mICP fabrication, thus reducing cost by alleviating the need for mask alignment as would be required if multiple masks were used. [17][18][19] The miniature ICP (mICP) was fabricated by etching planar spiral inductors in a copper-clad epoxy board. Another paper reports on the microfabrication and testing of monolithic mICP fab- ricated on glass wafers using surface micromachining.…”
Section: High-frquency Plasmasmentioning
confidence: 99%
“…A matching network was also microfabricated next to the load coil [48]. A one-mask fabrication process was used for the matching network and the mICP fabrication, thus reducing cost by alleviating the need for mask alignment as would be required if multiple masks were used [38][39][40]. The miniature ICP (mICP) was fabricated by etching planar spiral inductors in a copper clad epoxy board.…”
Section: Inductively Coupled Plasmas 1356-900 Mhzmentioning
confidence: 99%
“…Small sized microfabricated ICPs (mICP) have been developed in the last years [37][38][39][40][41][42][43][44][45][46][47]. Although large-size ICP's are typically operated at a frequency of 13.56 MHz, it has been shown that the optimum frequency for plasma generation increases to 460 MHz when the coil diameter is reduced to 5 mm [38].…”
Section: Inductively Coupled Plasmas 1356-900 Mhzmentioning
confidence: 99%
“…Miniaturized plasma sources include dc microhollow cathode discharges, 3 ac plasma displays, 4 microwave, 5 and rf inductively coupled plasmas. 1,2 Miniaturized inductively coupled plasmas ͑mICP͒ are a scaled down version of the ICPs used for large scale manufacturing of microelectronic devices. 6 Due to their small size ͑ϳmm͒, several adjustments have to be made in the operating conditions of mICPs.…”
Section: Introductionmentioning
confidence: 99%